A hog feeding experiment - Haney, John George (My University, 1899)
Introduction: All hog raisers who are abreast of the times know that there has been a very great change during the past few years in the class of hogs demanded by the market. This change has not come without cause, nor has it been sudden and sweeping. It has, however, made its appearance, and is still lingering among the backwoods farmers. A few years ago, the farmer kept his hogs until two and three and even four years old, fattened them out on corn at from four to six hundred pounds per head, and received the top of the market for them. The hog raiser now knows that his profitable hog is sold on the market at a weight of from 180 to 225 pounds, and the quicker he can get his hogs to that weight the more profitable it is for him. The farmer has been brought to a realization of this fact in several ways.
Citation: Haney, John George. A hog feeding experiment. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Source and Qualityof Hogs; Dividing into Lots; Preliminary Feeding and Weighing; Theses; Manuscripts (documents)